2021
DOI: 10.3389/fpsyg.2021.592513
|View full text |Cite
|
Sign up to set email alerts
|

The Home Learning Environment in the Digital Age—Associations Between Self-Reported “Analog” and “Digital” Home Learning Environment and Children’s Socio-Emotional and Academic Outcomes

Abstract: We analyzed the association between the analog and the digital home learning environment (HLE) in toddlers’ and preschoolers’ homes, and whether both aspects are associated with children’s social and academic competencies. Here, we used data of the national representative sample of Growing up in Germany II, which includes 4,914 children aged 0–5 years. The HLE was assessed via parental survey that included items on the analog HLE (e.g., playing word games, reading, and counting) and items on the digital HLE (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…These findings align with those by Meroni et al ( 2021 ), who – although considering socio-emotional skills of 11-year-old children – found a negative effect of video-screen time on emotional problems of 11-year-old children, but no effects on their prosocial skills or peer relationships. Interestingly, Lehrl et al ( 2021 ) found no associations between digital HLE-activities with socio-emotional skills for toddlers, but, for preschoolers, digital HLE-activities were related to weaker socio-emotional skills. These findings might be associated with the fact that, amongst others, interactions with digital media by older children are less often guided by parents (Lehrl et al, 2021 ), who also vary in the provision of these regulations, and suggest the need to explicitly consider parental regulation of the use of digital media.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings align with those by Meroni et al ( 2021 ), who – although considering socio-emotional skills of 11-year-old children – found a negative effect of video-screen time on emotional problems of 11-year-old children, but no effects on their prosocial skills or peer relationships. Interestingly, Lehrl et al ( 2021 ) found no associations between digital HLE-activities with socio-emotional skills for toddlers, but, for preschoolers, digital HLE-activities were related to weaker socio-emotional skills. These findings might be associated with the fact that, amongst others, interactions with digital media by older children are less often guided by parents (Lehrl et al, 2021 ), who also vary in the provision of these regulations, and suggest the need to explicitly consider parental regulation of the use of digital media.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Lehrl et al ( 2021 ) found no associations between digital HLE-activities with socio-emotional skills for toddlers, but, for preschoolers, digital HLE-activities were related to weaker socio-emotional skills. These findings might be associated with the fact that, amongst others, interactions with digital media by older children are less often guided by parents (Lehrl et al, 2021 ), who also vary in the provision of these regulations, and suggest the need to explicitly consider parental regulation of the use of digital media. Notably, Lehrl et al ( 2021 ) distinguished between prosocial behaviour and total difficulties score of the SDQ, while in the present study prosocial behaviour and peer relationships were considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These contexts range from the proximal such as the family and home environments, to the more distal settings of schools, communities, and governmental jurisdictions ( Bronfenbrenner and Morris, 2006 ). Within the home, the transactional dyad between home and school has been described as the Home Learning Environment (HLE), where child access and interaction with educational resources at home predicts academic outcomes (for example, Lehrl et al, 2021 ). Research has generally found support for a significant correlation between HLE and longitudinal academic outcomes, even where enhancements to the HLE are domain incongruent.…”
Section: Introductionmentioning
confidence: 99%